Electrocardiographic pattern of apparently healthy African adolescent athletes in Nigeria - Ogochukwu J. Sokunbi; Christy A. N. Okoromah; Ekanem N. Ekure; Olajide A. Olawale; Wuraola S. Eke (BMC, 2021)
Abstract Background Strategies to prevent sudden cardiac death (SCD) among young athletes have become topical worldwide and unrecognized cardiac pathology has been identified as a leading cause. Black ethnicity has been reported as an independent predictor of abnormal electrocardiography (ECG) findings among athletes and the frequency and significance of training-related ECG findings versus findings suggestive of an underlying pathology in the young African athletes is crucial. Methods This cross sectional study aimed to determine the prevalence and distribution of ECG patterns in young athletes and controls. A total of 360 participants (180 athletes and 180 controls) were recruited from six secondary schools in Lagos, Nigeria between November 2014 and July 2015. Evaluation included interviewer-administered questionnaires for relevant history, physical examination and resting 12 - lead ECG for each participant. Results Abnormal ECG patterns were found in 48.3% of athletes and 35.6% of controls. Training-related ECG findings occurred in 33.3% of athletes and 18.3% of controls. Athletes and controls had 7.7% prevalence of training un-related ECG patterns respectively. Left ventricular hypertrophy was the most common ECG finding among the athletes and male athletes had a higher prevalence of ECG abnormalities compared to females. Conclusion Adolescent athletes in Nigeria have a high prevalence of training-related ECG patterns and athletes and non-athletes alike have similar proportions of ECG findings suggestive of underlying structural heart disease. Cardiovascular evaluation including ECG should be performed for young athletes prior to competition at any level and should also be considered as part of pre-school entry assessment for all children.